2019
DOI: 10.1021/acs.langmuir.8b03633
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics at PDMS-E Emulsion Droplet–Gelatin Interface

Abstract: In this work, interfacial reaction kinetics between α-[3-(2,3-epoxypropoxy)­propyl]-ω-butyl-polydimethylsiloxane emulsion droplets with different sizes and gelatin was studied. The results of amino conversion rate determination show that the reaction proceeded in two steps. Fluorescence spectra analysis indicates that step 1 (0–2 h) should be the adsorption of gelatin on droplet surface. In step 2 (2–13 h), amino conversion rate increased rapidly. The reaction rate in step 2 (k 2) was obtained by using the 2nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…8−12 We had studied the preparation of monodisperse emulsion droplet of α-[3-(2,3-epoxypropoxy) propyl]-ω-butylpolydimethylsiloxane (PDMS-E) and investigated the influence of the size of PDMS-E droplet on the interfacial chemical reaction with gelatin. 13,14 During these study, we found that the adsorption of gelatin onto the surface of the PDMS-E droplet may be an important factor affecting the interfacial chemical reactions.…”
Section: ■ Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…8−12 We had studied the preparation of monodisperse emulsion droplet of α-[3-(2,3-epoxypropoxy) propyl]-ω-butylpolydimethylsiloxane (PDMS-E) and investigated the influence of the size of PDMS-E droplet on the interfacial chemical reaction with gelatin. 13,14 During these study, we found that the adsorption of gelatin onto the surface of the PDMS-E droplet may be an important factor affecting the interfacial chemical reactions.…”
Section: ■ Introductionmentioning
confidence: 93%
“…In the heterogeneous reaction system of polymers, the preparation of monodisperse latex particles with uniform size does not only enable reactions with increased efficiency and under milder reaction conditions but also avoids the influence of confinement effect caused by the change of particle size on its structure, so that the overall structure and properties can be successfully reproduced repeatedly . Therefore, the preparation and surface chemical modification of monodisperse emulsion particles has become a hot spot in the research of oil–water interface chemical reactions during the recent years. We had studied the preparation of monodisperse emulsion droplet of α-[3-(2,3-epoxypropoxy) propyl]-ω-butyl-polydimethylsiloxane (PDMS-E) and investigated the influence of the size of PDMS-E droplet on the interfacial chemical reaction with gelatin. , During these study, we found that the adsorption of gelatin onto the surface of the PDMS-E droplet may be an important factor affecting the interfacial chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation